Developing a screw conveyor in radio frequency systems to improve heating uniformity in granular products - Zhou, Hongxue; Wang, Shaojin (International Journal of Agricultural and Biological Engineering, 2019)
Radio frequency (RF) treatments have been increasingly studied due to the rapid heating, deep power penetration depth and high energy efficiency. However, the major challenges for commercial RF applications are non-uniform and run-away heating. The purpose of this study was to improve RF heating uniformity in three granular products (soybean, corn, and peanut) using a custom-made screw conveyor with sample movement and mixing. The results showed that soybean, corn and peanut samples in the screw conveyor were RF heated in a similar heating rate under the selected electrode gap and screw rotation speed, and the variations between the highest and lowest temperatures in the three samples were all clearly reduced as compared to the stationary treatments. The RF heating uniformity index was also reduced for soybean, corn, and peanut during and after the RF treatment. Therefore, the screw conveyor could improve RF heating uniformity due to stable, continuous, uninterrupted movement and mixing of samples. The small-scale screw conveyor used in RF systems would provide a solid basis for further large-scale industrial applications. Keywords: radio frequency (RF), screw conveyor, heating uniformity, movement, mixing DOI: 10.25165/j.ijabe.20191203.4227 Citation: Zhou H X, Wang S J. Developing a screw conveyor in radio frequency systems to improve heating uniformity in granular products. Int J Agric & Biol Eng, 2019; 12(3): 174–179.